Van der Waals interaction between surface and particle with giant polarizability - Makhnovets, K.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
We show that a nanoparticle with a “giant” polarizability α (i.e., with the polarizability volume α′ = α/4πε₀ significantly exceeding the particle volume) placed in the vicinity of a surface experiences a strongly increased van der Waals force at distances comparable or smaller than the characteristic scale R₀ ∝ (α′ )¹/³. At distances close to R₀, the oscillation mode of the particle dipole moment softens, so nonlinear polarizability must be taken into account to describe the particle-surface interaction. It is shown that a proper treatment of nonlinear effects results in the van der Waals force that is free of divergences and repulsive contributions.